Pengetahuan dan kecekapan pelajar kejururawatan dalam menggunakan skala koma glasgow - Noor Hazwaniha, Jafri (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
The Glasgow Coma Scale was devised by Teasdale and Jennett in 197 4 to standardize the assessment of patients with head injuries and neurological disorders such as cerebrovascular accidents and meningitis. It has been used in variety of clinical situations to assess neurological changes in patients. This quantitative study was carried out to explore nursing students' knowledge, competency and their attitudes in using the Glasgow Coma Scale. This is due to lack of studies done among nursing students related to this matter. The relationship between duration of clinical posting and competency of nursing students' in using Glasgow Coma Scale was also discussed in this study. Cross-sectional, descriptive research design was used in this quantitative study using a questionnaire as the instrumentation. Nursing students from diploma and bachelor degree program who undergone clinical posting in Hospital of University Science Malaysia was chose as sample population. Only a total of 100 questionnaires (n=100) were distributed, compared to 176 respondents who supposed to take part in this research according to sample size calculation due to time limitation. Descriptive values of the variables were expressed as frequencies, percentages and means. Chi-Square test was used to analyze the relationship between duration of clinical posting and competency of nursing students' in using Glasgow Coma Scale using the Statistical Package for the Social Sciences for Windows (SPSS) Version 12 software. From this study, mean score of the knowledge about Glasgow Coma Scale among nursing students were at moderate level (74.30%), mean score of the competency (70.30%) while mean score of their attitudes towards this scale were at the high level that is 94.50%. The p value< 0.05 (p=0.004), shows that the duration of clinical posting does influence the competency of nursing students in using the Glasgow Coma Scale. An initiative should be taken to enhance nursing students' level of knowtedge and competency in using this scale since they will be facing a variety of neurological disorders when they work in the future. This is very important to make sure that they can apply their theoretical knowledge along with their practical skills. Nursing institutions should monitor this situation seriously so that an effective teaching strategy can be implemented to increase theoretical knowledge as well as practical skills related to Glasgow Coma Scale. It is crucial to ensure that nursing students will be able to use the scale competently while minimizing errors when using the scale.